The effect of plastic debris attachment to the health of branching corals in Kelapa Dua Island, Thousand Islands. Issue 1 (May 2021) - Muhammad, F; Zamani, N P; Ismet, M S
Abstract: Plastic marine debris are a potential threat to the life of marine organisms such as corals. This study aimed to analyze the effect of different plastic waste attachments on the bleaching rate and the health of branching corals at Kelapa Dua Island. Branching coral colonies consisted of 15 fragments of Porites cylidrica at the water depth of 80-90 cm, then treated with plastic waste (control, clear plastic, sack plastic, packaging plastic, and black plastic) for four days. Determination of color changes in corals was determined using Adobe Photoshop CC 2019 and Image j software to obtain the area of the discoloration. The treatment with black plastic became most impactful, with a discoloration area of 5.33 ± 0.48 cm 2 and a healthy percentage of 73.62 ± 2.00%. Results of the linear regression between coral discoloration rate and light intensity showed a negative correlation, with r = -0.77 and R 2 = 0.59, then between the percentage of coral health and light intensity showed a positive correlation, with r = 0.83 and R 2 = 0.69. These results indicated that the decrease in light intensity due to the covered plastic debris affected the discoloration rate and the health percentage of branching coral.